Existence Value of Post-Mining Conservation Area: A Contingent Valuation Study of Lati Petangis Grand Forest Park, East Kalimantan - Eni Rohkayati; Rahmawaty; Endang Hernawan (Environmental Pollution Journal, 2026)
Quantifying the existence value of post-mining conservation areas is essential for justifying their legal protection and securing conservation finance, yet such assessments remain scarce in Indonesian tropical settings. This study estimates the existence value of Lati Petangis Grand Forest Park (Tahura Lati Petangis/TLP), a conservation area established from former coal mining land in Paser Regency, East Kalimantan. The Contingent Valuation Method (CVM) with a Willingness to Pay (WTP) approach was applied to 96 visitor respondents. Results show a weighted mean WTP of IDR 178,486 per individual with an 87.5% participation rate. The existence value was estimated at IDR 21,284,188,625 for the visitor population and IDR 752,608,083 for surrounding local communities, yielding a combined total existence value of IDR 22,036,796,708 per year, equivalent to 2.29% of the total economic value under the moderate scenario. The high existence value reflects strong public support for preserving this post-mining landscape and provides empirical grounding for conservation policy and Payment for Ecosystem Services mechanisms at comparable restoration sites across Indonesia.